Analysis of Career-Advancement for Medical School Graduates During the COVID-19 Pandemic at a Chinese Teaching Hospital - Zhu, Xiaoyan; Xie, Mingxuan; Xia, Xiaobo; Li, Xiangping; Zhang, Le (Frontiers in Integrative Neuroscience, 2021)
The COVID-19 pandemic has led to widespread social and economic disruptions in the balance of labor market. Our study aims to analyze the career-advancement of medical school graduates during the COVID-19 pandemic and the associated influencing factors. We collected and compared the career-advancement data of medical school graduates at a Chinese teaching hospital from 2016 to 2020. A self-designed 20-element medical graduates employment questionnaire and a Chinese adaptation of the General self-efficacy scale were distributed by the Questionnaire Star platform. Univariate analysis (Pearson's Chi-square-test and Fisher's exact-test) and subsequent binary logistic regression were used. Findings demonstrated that the career-advancement rate of medical graduate students in 2020 is 71.3%, which is significantly lower than that for the preceding 4 years from 2016 to 2019 (p < 0.001). Of the 251 employed medical school graduates, 159 (63.3%) have signed an employment agreement or contract, 83 (33.1%) are pursuing continued education domestically, and 9 (3.6%) have offers from foreign institutions. Univariate analysis revealed statistical differences of medical graduates' employment among various specialties, oral defense completion, job search start date, CV submission times, participation in a probationary period, and self-efficacy. Significant predictors for successful employment were early job search and self-efficacy by logistic regression model (χ2 = 12.719, p < 0.001). Most medical graduates assumed that the COVID-19 pandemic had a major (40.6%) or moderate (48%) impact on career-advancement. The COVID-19 pandemic has profoundly impacted the career-advancement of medical school graduates in 2020. We should make adaptive changes to improve the career-advancement of medical graduates.